Running close to the wind - Rowland, Alexandra (Tor Publishing Group, 2024)
"Avra Helvaçi, former field agent of the Arasti Ministry of Intelligence, has accidentally stolen the single most expensive secret in the world--and the only place to flee with a secret that big is the open sea. To find a buyer with deep enough pockets, Avra must ask for help from his on-again, off-again ex, the pirate Captain Teveri az-Haffar. They are far from happy to see him, but together, they hatch a plan: take the information to the isolated pirate republic of the Isles of Lost Souls, fence it, profit. The only things in their way? A calculating new Arasti ambassador to the Isles of Lost Souls who's got his eyes on Avra's every move; Brother Julian, a beautiful, mysterious new member of the crew with secrets of his own and a frankly inconvenient vow of celibacy; the fact that they're sailing straight into sea serpent breeding season and almost certain doom. But if they can find a way to survive and sell the secret on the black market, they'll all be as wealthy as kings--and, more important, they'll be legends"--